Pengembangan media big book dalam pembelajaran membaca siswa kelas 1 SDN Karangsono 2 Kecamatan Kwadungan Ngawi - Astutik, Karti; Hadi, Panji Kuncoro; Ricahyono, Sigit (Universitas PGRI Madiun, 2023)
The goal of this project is to create big book media that will improve first-grade reading instruction for children at SDN Karangsono 2 in Kwadungan District during the 2022–2023 school year. The study attempts to efficiently handle students' reading challenges by utilizing the ADDIE approach (Analysis, Design, Development, Implementation, Evaluation). After undergoing extensive validation, the new product—which was created especially for struggling readers— scored 96.76% for content quality and 92.72% for media, demonstrating its excellent efficacy. With engaging and useful learning materials, the large book media promises to greatly enhance the reading abilities of Grade 1 children at SDN Karangsono 2, Kwadungan District. Teachers can better meet the different learning needs of their children and ensure comprehensive literacy development from an early age by using cutting-edge teaching tools such as big book media. The results of this study improve young students' overall academic achievement as well as reading teaching.Tujuan dari penelitian ini adalah untuk membuat media big book yang akan meningkatkan pembelajaran membaca kelas satu untuk anak-anak di SDN Karangsono 2 Kecamatan Kwadungan pada tahun ajaran 2022–2023. Studi ini berupaya untuk menangani tantangan membaca siswa secara efisien dengan memanfaatkan pendekatan ADDIE (Analisis, Desain, Pengembangan, Implementasi, Evaluasi). Setelah menjalani validasi ekstensif, produk baru ini—yang diciptakan khusus untuk pembaca yang mengalami kesulitan—mendapatkan skor 96,76% untuk kualitas konten dan 92,72% untuk media, yang menunjukkan kemanjurannya yang luar biasa. Dengan materi pembelajaran yang menarik dan bermanfaat, media buku berukuran besar diharapkan dapat meningkatkan kemampuan membaca anak kelas 1 SDN Karangsono 2 Kecamatan Kwadungan secara signifikan. Guru dapat lebih memenuhi berbagai kebutuhan belajar anak-anak mereka dan memastikan pengembangan literasi komprehensif sejak usia dini dengan menggunakan alat pengajaran mutakhir seperti media buku besar. Hasil penelitian ini meningkatkan prestasi akademik siswa secara keseluruhan serta pengajaran membaca.